CAD technologies under thermal properties analysis of wall cladding of framed buildings. (December 2018) - Bedov, A I; Gabitov, A I; Gaisin, A M; Salov, A S; Chernova, A R
Abstract: Problems of energy-saving and efficient use of resources are currently becoming as important ones. Heat losses reduction in buildings deemed as end-use energy consumers is one of the most promising directions of energy saving. The aim of this analysis was the calculation of thermo technical characteristics of multi-storey residential building with reinforced concrete frame by simulating external walls using ANSYS software. 25-storey residential building with reinforced concrete frame in Ufa, the Republic of Bashkortostan was taken as the subject of research. Values of specific heat loss were obtained through the structural units and enclosure, on the whole, being reviewed, comparative results between calculations of main thermo technical characteristics of framed building was assessed by ANSYS software and by simplified table method as per SP 230.1325800.2015. Analysis of the air space inside the wall affecting specific heat loss through the junction with floor slab (perforation filled with heat insulation) has indicated that the air space inside the structure do not actually influence the heat loss for the low density blocks. Application of current software complexes like ANSYS is demonstrated as likely to be used for detailed scientific analysis of the possibility to increase enclosures thermal homogeneities. ANSYS may be used together with reference tables for specific heat loss for the junction between perforated floor slabs with the filler wall considering the air space inside it.